Postcards from the trenches negotiating the space between modernism and the First World War - Booth, Allyson (Oxford Univ. Press, 1996)
In Postcards from the Trenches, Allyson Booth traces the complex relationship between British Great War culture and modernist literature and architecture. By drawing on a wide range of materials and attending to the places where they overlap, Booth uncovers ways in which modernism is deeply embedded in a broader Great War culture. She links, for example, the modernist representation of an unstable self to soldiers' familiarity with corpses, the modernist mistrust for fact to the competing nationalist discourses of August 1914, and the modernist description of buildings as having shaken off the past to a desire to forget the war. Booth argues that the dislocations of war often figure centrally in modernist forms even when the war itself seems peripheral to modernist content. Thus she suggests that soldiers experienced the Great War as strangely modernist and that modernism itself is strangely haunted by the Great War.